Granger-couse effect on trading volume and stock return volatility: evidence from Malaysian ACE market - Maziah, Husin (2016)
This study analyzes the relationship between trading volume and stock return in Malaysian ACE market for the period of August, 2009 to December, 2015. Several tests were utilized; multivariate time series regression model; Brailsford model; VAR analysis, and; Granger-cause test. The empirical result proves a significant positive contemporaneous relationship between trading volume and stock return and vice versa. However, trading volume has negative significant relationship with stock return volatility, thus exhibits an asymmetry relationship between the variables. VAR analysis reveals that past trading volume has explanatory power in forecasting stock return and vice versa. And lastly, Granger-causality test indicates a significant bi-directional relationship between trading volume and stock return. Thus, it is proven that Malaysian ACE market is contradicted with the weak-form of efficient market hypothesis.